Effects of Sugammadex and Neostigmine on Post-operative Nausea and Vomiting in ENT Surgery - Mat, Nik Izyan Syaizana Nik; Yeoh, Chih Nie; Maaya, Muhammad; Zain, Jaafar Md; Ooi, Joanna Su Min (Frontiers in Medicine, 2022)
We aim to compare the effects of sugammadex on postoperative nausea and vomiting (PONV) with those of neostigmine-atropine mixture. A total of 136 American Society of Anesthesiology (ASA) I or II patients, aged 18 to 65 years old who underwent ear, nose, and throat (ENT) surgery under general anaesthesia were recruited into this prospective, randomized, double-blind study to receive either sugammadex 2 mg/kg or neostigmine 2.5 mg with atropine 1 mg for reversal of neuromuscular blockade. PONV scores and the need for rescue of anti-emetic were assessed upon arrival in the post anaesthesia recovery unit and at 1-, 6-, 12- and 24-hours post reversal. The incidence of PONV was significantly lower in patients who received sugammadex (3%) compared to patients who received neostigmine-atropine mixture (20%) at 6 hours postoperative (p = 0.013). Incidence of PONV was comparable at other time interval. None of the sugammadex recipients require rescue antiemetic while 2 patients from the neostigmine-atropine group required rescue antiemetic at 1 and 6 hours post reversal respectively. Need for rescue antiemetic was not statistically significant. We concluded that reversal of neuromuscular blockade with sugammadex showed lower incidence of PONV compared to neostigmine-atropine combination in the first 6 hours post reversal.